2022
DOI: 10.1038/s41467-022-28011-6
|View full text |Cite
|
Sign up to set email alerts
|

Completely aqueous processable stimulus responsive organic room temperature phosphorescence materials with tunable afterglow color

Abstract: Many luminescent stimuli responsive materials are based on fluorescence emission, while stimuli-responsive room temperature phosphorescent materials are less explored. Here, we show a kind of stimulus-responsive room temperature phosphorescence materials by the covalent linkage of phosphorescent chromophore of arylboronic acid and polymer matrix of poly(vinylalcohol). Attributed to the rigid environment offered from hydrogen bond and B-O covalent bond between arylboronic acid and poly(vinylalcohol), the yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
189
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(190 citation statements)
references
References 31 publications
1
189
0
Order By: Relevance
“…Huang and coworkers found that the presence of water molecules can enhance hydrogen bonding between CA matrices and TMA dopants, leading to remarkable elongation of phosphorescence lifetimes [38] . On the contrary, in the case of PVA matrices and 1,1’:3’,1’’‐terphenyl‐5’‐boronic acid, Li and coworkers reported that the water and heat treatment can destroy hydrogen bonding between matrices and dopants, causing the decrease of afterglow performance [100] . Both of these two‐component systems can be used as stimuli‐responsive afterglow materials.…”
Section: Promising Applications Of Organic Afterglow Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang and coworkers found that the presence of water molecules can enhance hydrogen bonding between CA matrices and TMA dopants, leading to remarkable elongation of phosphorescence lifetimes [38] . On the contrary, in the case of PVA matrices and 1,1’:3’,1’’‐terphenyl‐5’‐boronic acid, Li and coworkers reported that the water and heat treatment can destroy hydrogen bonding between matrices and dopants, causing the decrease of afterglow performance [100] . Both of these two‐component systems can be used as stimuli‐responsive afterglow materials.…”
Section: Promising Applications Of Organic Afterglow Materialsmentioning
confidence: 99%
“…[38] On the contrary, in the case of PVA matrices and 1,1':3',1''-terphenyl-5'-boronic acid, Li and coworkers reported that the water and heat treatment can destroy hydrogen bonding between matrices and dopants, causing the decrease of afterglow performance. [100] Both of these two-component systems can be used as stimuli-responsive afterglow materials.…”
Section: Stimuli-responsive Afterglow Materialsmentioning
confidence: 99%
“…Room-temperature phosphorescence (RTP) is traditionally associated with inorganic materials (including some minerals), where their afterglow lifetimes can extend from minutes to hours following photoexcitation. [1][2][3] Although inorganic RTP materials with prolonged light emission are actively being sought for many applications including optoelectronic devices, photocatalysis, and emergency signage, [4][5][6][7] they are less suitable for applications such as anticounterfeiting and bioimaging materials, where bright, subsecond afterglow is required. [8][9][10] In general, RTP is difficult to achieve at room temperature due to the spin prohibition of triplet exciton transitions and the fact that triplet excitons are easily quenched by oxygen and other nonradiative processes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] However, such materials are hard to acquire because of the limitation by the energy gap law. [ 11 ] Recently, phosphorescence resonance energy transfer (PRET) has emerged as an alternative which can endow suitable fluorescent organic dyes with long lifetime via a delayed sensitization process, [ 12 ] showing greatly potential applications in time‐resolved bioimaging, [ 13 ] multicolor afterglow materials, [ 14 ] information encryption, and anticounterfeiting. [ 15 ] For example, George and coworkers have reported an organic–inorganic scaffolding strategy which can be used as a light‐harvesting platform to achieve delayed fluorescence via PRET process.…”
Section: Introductionmentioning
confidence: 99%